Detection of Polycyclic Aromatic Hydrocarbons in Hide and Skin of Slaughtered Cattle and Goats in Anambra State, Nigeria - I.B. Ofomata; I.O. Nwankwo; A.J. Ogugua; E.V. Ezenduka; J.A. Nwanta; R.I. Obidike (Journal of Food Quality and Hazards Control, 2020)
Background: Polycyclic Aromatic Hydrocarbons (PAHs) are among hazardous chemicals that may endanger food safety. In Nigeria, hides and skins of animals are edible and used in dishes. So, this study investigated the levels of PAHs in singed and unsinged hides and skins of animals slaughtered at three districts abattoirs (Obosi, Uga, and Kwata) in Anambra State, Nigeria. Methods: Using gas chromatography, the levels of PAHs were determined in 120 samples of raw and singed cattle hides and goat skins. Data were analyzed using the SPSS Windows software package (version 20.0). Results: The total PAHs of raw and singed cattle hides were respectively 0.80 and 12.33 µg/kg for Obosi district, 0.56 and 6.96 µg/kg for Uga district, and 8.30 and 16.24 µg/kg for Kwata district. Furthermore, the total PAHs levels in raw and singed goat skins were respectively 2.75 and 9.00 µg/kg for Obosi district, 1.76 and 6.42 µg/kg for Uga district, and 1.30 and 5.19 µg/kg for Kwata district. The levels of some PAHs in singed hides and skins were significantly (p<0.05) higher than the unsinged samples. Conclusion: The materials used in singeing may increase the concentration of PAHs in singed hide and skin. Although, the known carcinogenic PAHs in the samples were below the maximum permissible level, it is probably of public health concern due to the associated health risk on cumulative exposure via the dietary consumption of such contaminated local meals.